2020
DOI: 10.1002/adhm.202001286
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Continuous Glucose Monitoring Using a Fluorescence‐Based Biocompatible Hydrogel Glucose Sensor

Abstract: Fluorescence‐based hydrogel glucose sensors with boronic acid‐based glucose recognition are promising regarding their potential to improve continuous glucose monitoring by facilitating long‐lasting accuracy. However, these sensors typically become encapsulated after implantation, and the dynamic range decreases following long‐term implantation and use. Herein, a four‐arm polyethylene glycol (PEG) hydrogel is developed with an immobilized glucose‐responsive fluorescence dye (GF‐PEG‐gel); this hydrogel is effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…A number of hydrogel-based sensor systems have been demonstrated for specific target biomarkers including ions, , glucose, , pH, , DNA, , bacteria, , and proteins. , Recently, the surface plasmon resonance (SPR) technique has been intensively utilized to detect biomarkers because of its high sensitivity. We also demonstrated that SPR and bioresponsive pNIPAm- co -AAc microgels can be employed to develop a highly sensitive biosensor by intensifying signals from multivalent protein binding (MPB) events of target molecules . MPB-capable microgels on an SPR chip were exposed to either antibodies or small multivalent cations that generate MPB events by complexing with their binding moieties, while nonspecific and monovalent binding events yield significantly lower signals than MPB events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of hydrogel-based sensor systems have been demonstrated for specific target biomarkers including ions, , glucose, , pH, , DNA, , bacteria, , and proteins. , Recently, the surface plasmon resonance (SPR) technique has been intensively utilized to detect biomarkers because of its high sensitivity. We also demonstrated that SPR and bioresponsive pNIPAm- co -AAc microgels can be employed to develop a highly sensitive biosensor by intensifying signals from multivalent protein binding (MPB) events of target molecules . MPB-capable microgels on an SPR chip were exposed to either antibodies or small multivalent cations that generate MPB events by complexing with their binding moieties, while nonspecific and monovalent binding events yield significantly lower signals than MPB events.…”
Section: Introductionmentioning
confidence: 99%
“…A number of hydrogel-based sensor systems have been demonstrated for specific target biomarkers including ions, 21,22 glucose, 23,24 pH, 25,26 DNA, 27,28 bacteria, 29,30 and proteins. 31,32 Recently, the surface plasmon resonance (SPR) technique has been intensively utilized to detect biomarkers because of its high sensitivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One study reports a scheme for measuring glucose concentration in rat and pig models using a wireless implantable device that incorporates a glucose-responsive fluorescent dye into a four-arm polyethylene glycol hydrogel (GF-PEG-gel). 42 The GF-PEG-gel mounts on top of a lightemitting diode (LED) and a photodiode (PD) for excitation and fluorescence detection, respectively. The hydrogel effectively mitigates foreign body reactions and suppresses fibrous capsule formation based on mechanisms described previously, thereby minimizing any diffusive delays in sensing.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Furthermore, fluorescent dyes sensitive to physiological parameters, such as glucose and pH (Figure a), can be immobilized in surface hydrogel coatings, where they can interact with ions, molecules, and proteins in the biological environment as the basis for sensing. One study reports a scheme for measuring glucose concentration in rat and pig models using a wireless implantable device that incorporates a glucose-responsive fluorescent dye into a four-arm polyethylene glycol hydrogel (GF-PEG-gel) . The GF-PEG-gel mounts on top of a light-emitting diode (LED) and a photodiode (PD) for excitation and fluorescence detection, respectively.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The reaction with ferricyanide on the testing strip produced ferrocyanide, the base of the blood glucose reading [243]. A fluorescence-based hydrogel glucose invasive sensor is another example tested in vitro and in vivo (on pigs over 45 days) [244]. The device comprised two units: one implantable and one external.…”
Section: Glucose Sensorsmentioning
confidence: 99%